Case of Warthin Tumor with Squamous Metaplasia: A Recent Appraisal in the World Health Organization Classification System for Head and Neck Tumors - Jha, Tanvi; Gupta, Prajwala (Annals of Pathology and Laboratory Medicine, 2025)
Fine needle aspiration cytology (FNAC) is commonly employed to diagnose salivary gland tumors due to its minimally invasive nature. However, repeated FNAC can lead to complications such as vascular injury, ischemia, and infarction, particularly in Warthin tumors (WT). These changes manifest as squamous metaplasia, necrosis, and inflammation, which can mimic malignancy, leading to diagnostic confusion. We present a case of infarcted WT in a 54-year-old male with left parotid swelling, where FNAC showed oncocytic and squamous metaplastic cells, raising concerns for squamous cell carcinoma.